Linguistic commitment in current Spanish poetry: From the dissolution of experience to new names (María de la Cruz and Laura Rodríguez Díaz). - Molina Gil, Raúl; López Fernández, Álvaro (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article aims, on the one hand, to show the validity and continuity of an experimental tendency, based on the dislocation and restructuring of language, in Spanish poetry of the last decade; and, on the other hand, to identify some of its distinctive features today. To this end, in the first part of the article we will review the keys to this continuity, the approaches that academic criticism has taken to the phenomenon, its main poets, the impact of its linguistic commitment and its presumed obscurity, the importance of its publication and dissemination platforms, etc. Then, in the second part of the article, we will undertake a contrasted analysis of the collections of poems Los clavos que dan nombre a la metralla (2019), by María de la Cruz, and San Lázaro (2021), by Laura Rodríguez Díaz, two of the youngest representatives of this deconstructive trend. Their collated reading will allow us to recognize and study some of the most relevant motifs, intertextualities, referents and expressive tensions of their latest manifestations.